Knowledge and Practice of Social Responsibility among Women Entrepreneurs in Akoko Land, Nigeria - Oluwatoyin Dorcas Ayimoro; Oluwatosin Ruth Obi (Randwick International of Education and Linguistics Science Journal, 2020)
The main thrust of this study is to investigate the knowledge of social responsibility (SR) and the practice among women entrepreneurs of Akoko land. With the surge in entrepreneurial activities among women and the attendant peculiarities of production and marketing, the study sought to find out (i) What knowledge women entrepreneurs have on SR (ii) Do they practice social responsibility at all? and (iii) the impediments towards the practice. It does this through a qualitative method of Focus Group Discussion among 220 women entrepreneurs in the four Local Government Areas of Akoko land - Akoko North- east, North-west, South- east and South- west in the production of cassava flour, palm oil, locust bean and cellophane bags. Findings revealed that the women entrepreneurs displayed a skewed knowledge of SR in their act of communalism and philanthropy. The study therefore, recommends that there is the need to sensitize women entrepreneurs on a good understanding of SR to impact on them the responsibility of business ethics and also promote sustainable development.